New attempts at Electronic Documents in Transport. Bolero - the end of the experiment, the beginning of the future? - Gehrke, Florian (Department of Commercial Law, 2014)
In this thesis the author examines a 'revolution' taking place in the shipping industry brought on by the development of computerisation, electronic commerce and the change from paper documentation to electronic documentation in the carriage of goods by sea. The focus of the paper is on Bolero, a project of the European Community beginning in the early 1990s and which has been used commercially since September 1999. In this paper the author follows the Bolero project from its inception as an experiment through to its commercial application. The question is asked to what extent Bolero has become an alternative to, or in fact replaced paper documentation in the carriage of goods by sea. As an introduction the author looks at the paper bill of lading and other forms of sea transport documentation with a focus on their advantages and disadvantages. He then examines the development of EDI and paperless sea transport documentation, in particular Bolero and the history of its development. Following this is an in depth investigation of the Bolero system in its current form, the contractual relations involved and the position of Bolero in the surrounding legal framework in a South African and international context. Finally the author looks at the future of Bolero as a commercial enterprise.